RUMAH SAKIT STROKE DI PEKANBARU DENGAN PENDEKATAN ARSITEKTUR PERILAKU - Rohaniah, Lathifah; Aldy, Pedia; S, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Stroke Hospital is special facilities for stroke that do not exist in Pekanbaru yet, the design of this hospital can accommodate the patient activity based on the pattern of stroke behavior. This is generally divided into two, such as slow and impulsive behavior. The problems are solved by applying the principles of behavior architecture as an approach in design, they are environmental perceptions and personal space. Methods use are incude field data collection, literature study, empiris study, and stroke behavior analysis by using behavior mapping methods, the methods are place center mapping and person center mapping. The result of this study is able to design the stroke hospital that focus on the behavioral problems of stroke patients which is set by using concept of Healing Environment, this concept designs a hospital environment that can help improve the cure and adaptability of patients by applying the healing element and requesting the stroke patient space in accordance with their personal space. The design is also planned as a refference for other hospital with the most complete stroke facility in Pekanbaru.Keywords : Hospital, Behavior Architecture, Stroke Behavior